Dimensional Change of Laser-Welded Gold Alloy Induced by Heat Treatment - Ikuya Watanabe, DDS, PhD;1 Jennifer Chang, DDS;2 and Yvonne Chiu, DDS 2 (Journal of Prosthodontics, 2007)
This study examined the effects of laser welding and heat treatment on the dimensional change of cast gold alloy frameworks